Meta-Analysis: The Effect of The Problem Based Learning Model in Improving Students' Mathematical Literacy - Ni’matul Janah; Zaenuri; Scolastika Mariani; Isnaini Rosyida (EduMa: Mathematics education learning and teaching, 2025)
Mathematical literacy is important to help students solve problems in real life, but the achievement of Indonesian students is still low. The Problem Based Learning model is considered effective in improving mathematical literacy because it focuses on solving real problems and student activities. This study aims to analyze the effect of the Problem Based Learning model on improving students' mathematical literacy through a Meta-Analysis approach to five nationally accredited articles published in the 2020-2025 period. Based on the calculation results, the average pretest score was 45.85 and the posttest score was 75.58, so there was an increase after the Problem Based Learning model implementation. The average effect size in the high category, as determined by the effect size computation, was 2. 042. According to the t-test findings, before and after the Problem Based Learning approach was implemented, there was a noticeable change in the average scores of students' mathematical literacy on the pretest and posttest, specifically the calculated t value > t table = 7.530 > 1.656 This study's findings suggest that the issue is Mathematical literacy is significantly enhanced by based learning. However, several studies have shown that success is influenced by grade level and supporting media such as Geogebra and e-LKPD. Therefore, Problem-Based Learning can be a highly effective learning alternative for improving mathematical literacy. Its implementation needs to be continuously developed, taking into account learning design, technology integration, and teacher readiness to ensure optimal and sustainable results.